Use of modified silica gel for concentrating Pb (II) and Cd (II) occurring in form of complex anions - Déniz, Rubén del Toro; Echevarría, Marlene Seijo; Terra, Zaida Fernández; Espinosa, Ana María Peón; de Moya, Humberto Varela (Eclética Química, 2007)
The performance of silica gel, modified by the impregnation with a high molecular weight quaternary amine (triethyl octadecyl ammonium iodide), used for the concentration of heavy metals occurring in water is studied. The material under study captures Cd, Pb, which are capable of forming stable complexes with I - ions.The results obtained about the metal capture, under dynamic conditions, are described and metal ions are removed by desorption with EDTA and quantified by AAS.